Formation of Docetaxel-related Substances in the Polymer Particles During Storage and Gamma-treatment - Yu. I. Poltavets; S. V. Aleshin; V. V. Zavarzina; A. I. Murav’eva; A. A. Soboleva; I. A. Tubasheva; S. L. Kuznetsov (Разработка и регистрация лекарственных средств)
Introduction. Docetaxel is widely used for cancer treatment. Actual issue for newly developed polymer-based Docetaxel formulations is applicability of current quality requirements. The technology of polymeric forms, including gamma-sterilization, are differ from actual Docetaxel injections technology. In this study were used PLGA-based particles with Docetaxel. The main attention was directed to studying qualitative and quantitative content of related impurities in polymeric forms during long-term storage and gamma-sterilization in comparison with pharmacopoeial requirements for Docetaxel injections.Aim. Studying of possible patterns of Docetaxel-related impurities formation between intact and gamma-irradiated batches.Materials and methods. Objects of study – lyophilizates of Docetaxel polymeric forms was previously obtained by the authors. Qualitative and quantitative analysis was performed by high pressure liquid chromatography.Results and discussion. Docetaxel-related impurities was determined and evaluated in the intact and gamma-treated batches. It was cleared, that related substances in the gamma-treated batches was different in comparison with non-treated but after vary storage periods.Conclusion. Docetaxel-loaded polymeric drugs shown proper stability during long term storage. The influence of gamma-treatment to Docetaxelrelated impurities content was found. Gamma sterilization can be promising method for novel drugs, but it needs individual study in the each case.